RUSSIAN WORLD AND IT`S SIGNS IN THE “CORRESPONDENCE OF ANDREI KURBSKY WITH IVAN THE TERRIBLE” (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-80-93The theme of the ‘Russian World’ is permanent in national literature, and rather often it is closely connected with socio-political processes. The 16th century played a special role in the history of Russia, determining, to a great degree, the ways of further development of the country and posing significant political, philosophical, and social issues; the key historical figure of the period was Ivan the Terrible, whose reign is associated with the strengthening of an united centralized Russian state headed by Moscow and the expansion of the state.The discussions in his letters to Ivan the Terrible (the correspondence between Andrey Kurbsky and Ivan IV the Terrible of Russia) became a dispute about the Russian World. The correspondence reflected polar views on the same issues: the power and the figure of the ruler, the form of government, the ratio of statehood and the Orthodoxy, the loyalty of subjects to the ruler. The discussions in the letters of Kurbsky and Ivan the Terrible form a special image of the ‘Holy’ Russian Land, the ‘Kingdom of God’, and the phrase ‘the Russian land’ is used in the correspondence in the civilization sense. The message of Ivan the Terrible reflects the motive of the selection of Russia as a stronghold of the Orthodoxy; the Tsar speaks about the protection of the Orthodox faith by any means, even the cruelest ones. Autocracy, according to Ivan the Terrible, is inseparable from the Orthodox Christianity. The dialogue between the tsar and the prince is considered in the context of the opposition lines of ‘mine or ours, my or our own’ – ‘alien’, ‘the Russian world’ and ‘non-Russian one’: Kurbsky writes from abroad and is perceived as a traitor.The material of the letters highlights the signs and features of the Russian World as a special integral phenomenon: the Orthodoxy, selectivity, commonality and similarity of history and culture, Messianism.Key words: The Russian world, “Correspondence of Andrey Kurbsky with Ivan the Terrible”, the state, the Orthodoxy